Equivalent-Risk Class Hypothesis: An Empirical Study - Rao, N. Krishna (Journal of Financial and Quantitative Analysis, 1972)
Studies [1, 3, 4, 5] pertaining to the relationship between a firm's cost of capital and the debt component of its capital structure have been implicitly assuming the equivalent-risk class hypothesis to be true. According to the hypothesis, firms belonging to the same industry group do not exhibit significant differences in regard to business risk and can, therefore, be treated as belonging to an equivalent risk class. The validity of this hypothesis, as borne out by the research of Wippern [8] and, later, of Gonedes [2], has become questionable. The purpose of the present paper is to replicate the test carried out by Gonedes with a set of sampled data from Indian industries. A brief review of the two existing studies is given below.